Rare Cause of Late Recurrent Angina following Coronary Artery Bypass Grafting: Iatrogenic Aortocoronary Arteriovenous Fistula Causing Coronary Steal - Jayakumar Sreenivasan; Muhammad Ayub; Neha Yadav; Yasmeen Golzar (Case Reports in Cardiology)
Iatrogenic aortocoronary arteriovenous fistula is a very rare complication of coronary artery bypass grafting in which one of the arterial grafts inadvertently forms a fistulous tract with a cardiac vein, shunting blood from the anastomosed coronary artery. We report a patient with an iatrogenic left internal mammary artery graft to cardiac vein fistula presenting with recurrent angina three years after a three-vessel coronary artery bypass grafting.